(untitled) (Bangladesh Journal of Agricultural Research, 2022)
The present research empirically determined farm resource-input utilization among the groundnut farmers and the effect of agricultural policy on groundnut production in Niger State of Nigeria. A total of 120 farmers were selected through a multi-stage sampling technique. Thereafter, a structured questionnaire complemented with the interview schedule was the instruments used to elicit information from the respondents and the collected data were analyzed using inferential statistics and the policy analysis matrix (PAM). The empirical findings showed that groundnut production is affected by the failure of the farmers to apply the recommended inorganic fertilizer dosages. In addition, the farmers were not economically efficient as allocation of the farm inputs were not optimized. The farm size, seed, manure, biocides and depreciation on capital had an index of greater than 1.00 while NPK and human labour AEI index were less than 1.00. Furthermore, the agricultural policy was not in favour of the farmers despite the effort in deregulating the agricultural marketing sub-sector. Therefore, the study recommends that the extension agents should re-train the farmers on the appropriate technologies needed in the application of recommended dosage for agro-chemical, especially inorganic fertilizer. In addition, the government should improvise a protectionist policy for the producers so that they can compete favourable and earn remunerative prices in the agricultural commodity markets. Bangladesh J. Agril. Res. 45(4): 431-444, December 2020